2022
DOI: 10.21608/sjfop.2022.272767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Foliar Application of Gibberellic Acid and Liquorice Root Extract on Growth, Volatile Oil Yield Productivity and Antimicrobial Activity in Geranium (Pelargonium Graveolens L. Her.) Plants

Abstract: This work was carried out during the two successive seasons (2019/2020 and 2020/2021) in the Experimental Farm of Horticulture Research Station at Sids, Beni-Suef Governorate, to investigate the effect of foliar application of gibberellic acid (GA3) at 100, 200 and 300 ppm and spraying of two extractions of liquorice root (aqueous LRE at 5 and 10 g/l and ethanolic LRE at 5 and 10 g/l) and their interaction on the vegetative growth (plant height, number of branches, herb fresh weight per plant and per feddan), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…While nitrogen, phosphorus , potassium and total carbohydrates percentage the lowest values of these parameters by planting distances (20*20 cm) and F1 in two cuts and in second seasons. Also, the abovementioned data on Chemical composition are met with those attained by Khater et al (2020) on caraway plant, found that aloe extract produced the highest All, Chemical constituents, (Abdel-Mola et al 2022) on Pelargonium Graveolens, found that total carbohydrate, NPK increased with licorice extracts LRE. Hasan and Kader (2022) on Punica granatum interaction between NPK, and Licorice extracts led to significant increase, and gave the highest value of leaves content of nitrogen, phosphor and potassium.…”
Section: Table 2 Effects Of Planting Distances and Some Natural Plant...mentioning
confidence: 73%
See 2 more Smart Citations
“…While nitrogen, phosphorus , potassium and total carbohydrates percentage the lowest values of these parameters by planting distances (20*20 cm) and F1 in two cuts and in second seasons. Also, the abovementioned data on Chemical composition are met with those attained by Khater et al (2020) on caraway plant, found that aloe extract produced the highest All, Chemical constituents, (Abdel-Mola et al 2022) on Pelargonium Graveolens, found that total carbohydrate, NPK increased with licorice extracts LRE. Hasan and Kader (2022) on Punica granatum interaction between NPK, and Licorice extracts led to significant increase, and gave the highest value of leaves content of nitrogen, phosphor and potassium.…”
Section: Table 2 Effects Of Planting Distances and Some Natural Plant...mentioning
confidence: 73%
“…While the lowest values of these treatment scored by between planting distances (20*20 cm) and F1 in the two cuts and in both seasons. Also, the abovementioned results are met with those attained by, (Khater et al 2020) on Pelargonium Graveolens, found that with aloe extract produced the highest oil yield and oil percentage, Abdel-Mola et al (2022) on Carum Carvi, parameters on oil yield was augmented due to the high dose with aqueous LRE, Toaima et al (2022) on Ocimum basilicum L. Hassan (2023) on Carum carvi, licorice extract gave the highest, ratio of carvone, and limonene.…”
Section: Chlorophyll a B And Carotenoid's Contentsmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, the highest values of these parameters were recorded using the cotreatment between planting date (autumn) and T4 in the two seasons. Osman and Sewedan (2014) on Solidago canadensis, Sorour and El-Shanhorey (2016) on Dracaena marginata., Mohamed (2017) on aster , Elsadek et al (2020) on Codiaeum Variegatum L. , andAbdel-Mola et al (2022) on Pelargonium graveolens L., Reda et al, (2010) on chamomile plant , EL-Nemr (2018) on Dendranthema grandiflorium cvs., El-Kinany, et al (2019) on Gaillardia pulchella and . Abou El-Ghait, et al (2020) on Jasminum sambac plant cleared that the richest leaf nitrogen and phosphorus percentages were obtained by those treated with BA at 60 ppm + mineral fertilization at 6 g/pot in both seasons.…”
Section: Effect Of Planting Date Growth Stimulants and Their Combinat...mentioning
confidence: 99%